Myocardial infarction without obstructive coronary artery disease (MINOCA) - Klever Geovanny Cárdenas Chacha; Yeseb Janira Vera Torres; Antonella Fanny Montenegro Villavicencio; Amilkar Suárez; Shirley Abigail López Baños (Correo Científico Médico)
Introduction: Ischemic coronary artery disease is a common health problem that requires substantial resources from health care systems. The most common clinical phenotype has been obstructive atherosclerotic disease of the coronary arteries, which has now changed to the phenotype without coronary obstruction, MINOCA.